(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى تعرف مدى تضمن المهارات الحياتية في مادة الدِّراسات الاجتماعية للصفوف الثلاثة الأولى من مرحلة التعليم الأساسي، إضافة إلى الكشف عن مستوى تتابعها في الصفوف الثلاثة، وكيفية توزع مظاهرها السلوكية. ولتحقيق هذا الهدف أعدَّت الباحثة قائمة بالمهارات الحياتية الواجب تضمنها في مادة الدِّراسات الاجتماعية في هذه الصفوف، وأداة لتحليل المحتوى لاستخدامها في تحليل مقررات الدراسات الاجتماعية في ضوء المهارات الحياتية، واستُُخدم المنهج الوصفي التحليلي للإجابة عن أسئلة الدراسة. وأظهرت النتائج أنّ نسبة المهارات الحياتية في الصفوف الثلاثة قد بلغت (47.43%)،وجاءت مهارة اتخاذ القرار في المرتبة الأولى بنسبة مئوية(37.09%)، جاءت بعدها مهارة حل المشكلات بنسبة (28.16%)، بينما حصلت مهارة الحوار على نسبة مئوية (11.73%)، ثم جاءت مهارة العمل في جماعة بنسبة مئوية ( 10.79%)، وحصلت مهارة كسب الأصدقاء على نسبة (8.92%)، وجاءت مهارة إدارة الوقت في المرتبة الأخيرة بنسبة (3.28%). وتتابعت ثلاث مهارات منها في الصفوف الثلاثة، وهي: الحوار، اتخاذ القرار، حل المشكلات.وقد بلغت نسبة المظاهر السلوكية للمهارات الحياتية في الصفوف الثلاثة (44.82%). The Study aims at identifying the extent to which life skills are included in the social studies curriculum of the first three grades in Syria, in addition to discovering the level of their sequence, and how their behavioral aspects are distributed. To achieve this purpose, the researcher prepared a list of life skills that should be contained in social studies curriculum in these grades, and a content analyzing tool to use it in analyzing the social studies curricula. The descriptive analytical approach had been used.The results showed that life skills proportion in the three grades reached(47.43%), and the decision-making skill came in the first rank with a percentage of (37.09%) ,followed by the problem-solving skill by a percentage of (28.16%), while dialogue got a percentage of (11.73%), then working in group skill came as percentage of (10.79%), and make-friends skill got a percentage of (3.28%) ,and make-friends came in the final rank as a percentage(3.28%). Three skills of it followed in the three grades which are dialogue, decision-making, and problem-solving, detecting a mediating percentage of behavioral aspect for the life skills which was (44.88%).